Optimalisasi Program Police Goes to Pesantren dalam Mengurangi Pelanggaran Lalu Lintas oleh Santri di Wilayah Hukum Polres Garut - Kharis Dwi Irpan (Police Studies Review, 2021)
ABSTRACT This research is motivated by the high traffic violations that lead into potential accidents by Santri on Garut District Police jurisdiction. The level of material and moral damage caused by traffic accidents can aim to the deficit of national health and development. According to that, it is important for the Police to prioritize preventive measures in order to reduce them. Therefore, a study was carried out to find the picture of implementation and the factors influencing the Police Goes To Pesantren Program, which were held by Unitdikyasa of Garut District Police. This research was conducted using descriptive analysis research methods and qualitative approaches. The Police Goes To Pesantren Program then analyzed using Indonesian Police Chief Regulation Number 12 of 2012 and Indonesian Police Chief Regulation Number 23 of 2010, which considered to be not optimal because only some of the assessment indicators are fulfilled. Factors that become obstacles are, inter alia, internal and external factors including the human resources field, the facilities and infrastructure field, budgeting field, support for other functions in the police organization, cross-agency support, and pesantren support. Based on the results, the Authors provide suggestions that are in accordance with each theory used, namely the Theory of Management, Theory of Communication and Theory of Behavior-Learning to be adjusted into the Job Description and Unitdikyasa Satlantas Standard Operation Procedure, the Unitdikyasa personnel’s number addition, provides the needs of legal written work relation procedure between related functions and agency, repairs supervision system of Satlantas, regulates Dikmas vocational education, applies the concept of rewards and punishment, update the presentation material, and related research in accordance the Police Goes to Pesantren Program to these activities between and becomes specific analysis result, with evaluation materials in reducing traffic violation by Santri. Keywords: Police Goes To Pesantren, Santri, Unitdikyasa, Violation, Traffic